The Effect of Loading and Unloading Activities on the Comfort of Surrounding Communities Through the Environmental Impact (Air) of Tanjung Priok Port - Cecep Pahrudin; Gatot Wibisono; Albani Putra Djabbar; Raihan Dimas Maulana (Green Publisher, 2025)
This study aims to determine the impact of container loading and unloading activities on the community around Tanjung Priok Port, especially the impact of environmental pollution caused by loading and unloading activities that cause various negative impacts that have an impact on the level of comfort and public health. This research also aims to be a study material for central and regional planning between industrial activities, especially ports and community settlements. In this study, the method used is quantitative research method using SEM Path analysis research technique with a total of 100 respondents. The results showed that loading and unloading activities at Tanjung Priok port disrupted behavior patterns and community comfort. The central and local governments must have careful planning in regulating regional spatial planning and be firm in enforcing regulations related to the environmental impact of industrial activities, especially ports to minimize the impact caused.